Testing effects of partner support and use of oral contraception during relationship formation on severity of nausea and vomiting in pregnancy - Kateřina Roberts; Jan Havlíček; Šárka Kaňková; Kateřina Klapilová; S. Craig Roberts (BMC, 2023)
Abstract Background A recent study focusing on dietary predictors of nausea and vomiting in pregnancy (NVP) found that women with higher levels of partner support, and those who had used oral contraception (OC) when they met the father, both tended to report less severe NVP compared with previous non-users or those with less supportive partners. We provide a further test of these factors, using a large sample of women from four countries who retrospectively scored their NVP experience during their first pregnancy. Methods We recruited women who had at least one child to participate in a retrospective online survey. In total 2321 women completed our questionnaire including items on demographics, hormonal contraception, NVP, and partner support. We used general linear models and path analysis to analyse our data. Results Women who had used OC when they met the father of their first child tended to report lower levels of NVP, but the effect size was small and did not survive adding the participant's country to the model. There was no relationship between NVP and partner support in couples who were still together, but there was a significant effect among those couples that had since separated: women whose ex-partner had been relatively supportive reported less severe NVP. Additional analyses showed that women who were older during their first pregnancy reported less severe NVP, and there were also robust differences between countries. Conclusions These results provide further evidence for multiple influences on women's experience of NVP symptoms, including levels of perceived partner support.